Students’ Perceptions of Using YouTube as English Online Learning Media during Covid-19 Pandemic - Simanjuntak, Uli Sylphia; Silalahi, Dumaris E; Sihombing, Partohap S. R.; Purba, Lydia (JOLLT Journal of Languages and Language Teaching, 2021)
This study aims to analyze the students' perceptions in using YouTube as online English learning media during the Covid-19 pandemic. at grade XI of SMA Negeri 4 Pematangsiantar. The aspects of students’ perception cover attractiveness, effectiveness, relevancy, and motivation. These aspects are seen in students’ learning experiences in classes. The research subjects include students in class XI PMIA 6 and XI PMIA 7 at SMA Negeri 4 Pematangsiantar. The data are collected using qualitative research methods, namely the type of basic interpretive studies where the data are obtained using a questionnaire distributed to students in the form of a Google Form. The result of data analysis shows that most students gave a positive response to each statement in each aspect of the questionnaire given. Based on the research results obtained, this study can be concluded that the use of YouTube as an online English learning medium is attractive, effective, and relevant to the course content. It also motivates students in English online learning during the Covid-19 pandemic grade XI of SMA Negeri 4 Pematangsiantar.